Preschool in foreign countries - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Preschool education, also known as early childhood education, is an essential part f a child’s development. It is the education that children receive before they start rimary school and typically caters to children aged three to five years old. Preschool ducation varies from country to country, and each country has its unique approach o educating young children.